Socio-economic development of the Penipe canton thanks to the contribution of the agroindustrial sector - Ruiz Carrillo, Carolay Sleny; Bravo Ávalos, María Belén; Gavilanez Vega, María Isabel; Herrera Chico, María Fernanda (mktDESCUBRE; Vol 1 No Edición Es (2024): 7th International Scientific Congress of Administrative and Financial Sciences FADE 2023, 2024)
The processing sector is growing and developing new strategies to transform the raw material. Different mechanisms are being demonstrated to analyze these factors. Acquiring and implementing agro-industrial fields can be a good strategy due to the high potential of raw materials and resources that are used to maintain production levels. However, these mechanisms can also have negative consequences for the development of the local population if the relevant studies are not carried out. Penipe, a canton in the province of Chimborazo in Ecuador, stands out for its agricultural activity and is ideal for the production of food raw materials. The implementation of agro-industry in this place could improve the quality of life of its inhabitants and generate social, economic and material benefits. Agroindustry is an economic activity that is responsible for transforming and adding value to agricultural, forestry and biological products. It is of great strategic importance for the economic and social development of Ecuador, with high growth potential. Agro-industry is related to the transformation of raw materials from agriculture, forestry and fishing into other products or by-products. This activity has expanded thanks to state policy and planning, becoming a key engine for the country's economy. In Latin America, agro-industry has great social and economic importance. It responds to the basic needs of the population and is affected by trends such as the use of agricultural technology, which are reshaping its future and creating challenges and opportunities for the operations of organizations. The food shortage expected for the next few years is a major concern for agro-industrialists and companies involved in the food chain .